Quality Of Health Care In India: Challenges, Priorities, And The Road Ahead - Ausaf, Huma; Khan, Manzoor (Journal of Neonatal Surgery, 2025)
The quality of healthcare stands as a foundational element of public health policy and is embedded in India’s legal framework through both constitutional and statutory mechanisms. At the constitutional level, Article 21 of the Indian Constitution, guaranteeing the fundamental right to life, has been judicially interpreted by the Supreme Court of India to include the right to health as an essential component of a dignified existence. In Consumer Education & Research Centre v. Union of India, the Court underscored that the right to life extends to protecting the health of workers, viewing health as intrinsically linked to Article 21's protections.[1] Through these interpretations, the judiciary has created a legal basis for citizens to demand healthcare services that meet minimum quality standards. However, while this jurisprudential shift has fostered a strong normative framework, translating this right into actionable healthcare access encounters substantial challenges, both in terms of policy implementation and legislative oversight. India’s healthcare delivery remains encumbered by regional disparities, regulatory fragmentation, and limited enforcement of the Clinical Establishments Act, which is meant to standardize health facilities across the country.[2] Addressing these issues requires a robust legislative approach that integrates patient rights, strengthens regulatory bodies, and fosters accountability.[3] This paper aims to assess the current regulatory landscape, identify critical enforcement gaps, and recommend legal reforms that could enhance the quality and accessibility of healthcare services nationwide. [1] Consumer Education & Research Centre v. Union of India, AIR 1995 SC 922 [2] See “Clinical Establishments (Registration and Regulation) Act, 2010,” Government of India, for regulatory challenges and limitations in state adoption. [3] World Health Organization, “The Right to Health,” 2021.